2021
DOI: 10.1021/acsami.0c22761
|View full text |Cite
|
Sign up to set email alerts
|

Cu3BiS3/MXenes with Excellent Solar–Thermal Conversion for Continuous and Efficient Seawater Desalination

Abstract: Two-dimensional materials with unique physical and chemical properties have recently attracted widespread attention in the field of solar thermal conversion. However, affected by the Fresnel effect, traditional two-dimensional materials such as MXenes, graphene, transition metal disulfide often have relatively significant light reflection losses at the solid–liquid or gas interface. So how to improve the light absorption of the two-dimensional material performance has become a new challenge in photothermal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 62 publications
(75 reference statements)
1
45
0
Order By: Relevance
“…They are defined by the general formula M n +1 X n T x , 38 , 42 where T x represents the surface-terminated species (−F, −OH, or −O). 43 , 44 Owing to their unique properties, MXene nanosheets, particularly Ti 3 C 2 T x , have been employed as a photothermal coating for MD membranes, 45 benefiting from the pronounced surface plasmon (SP) oscillations at the surface of the nanosheets. 46 , 47 In principle, upon the light illumination of MXene membranes at wavelengths in resonance with these SPs, the temperature gradient generated across the membrane surges due to the intrinsic SP-assisted light-to-heat conversion.…”
Section: Introductionmentioning
confidence: 99%
“…They are defined by the general formula M n +1 X n T x , 38 , 42 where T x represents the surface-terminated species (−F, −OH, or −O). 43 , 44 Owing to their unique properties, MXene nanosheets, particularly Ti 3 C 2 T x , have been employed as a photothermal coating for MD membranes, 45 benefiting from the pronounced surface plasmon (SP) oscillations at the surface of the nanosheets. 46 , 47 In principle, upon the light illumination of MXene membranes at wavelengths in resonance with these SPs, the temperature gradient generated across the membrane surges due to the intrinsic SP-assisted light-to-heat conversion.…”
Section: Introductionmentioning
confidence: 99%
“…Tan et al studied the strain piezoelectric coefficient of La 2 CO 2 , a lanthanide MXene material, under axial strain. They reported that strain piezoelectric coefficient of this material is up to 22.32 pm/V, which is substantially higher than that of other known piezoelectric materials, such as Sc 2 CO 2 , Y 2 CO 2 , BN, GaAs, and AlSb ( Chen et al, 2021 ; Wang et al, 2021b ). Bai et al reported that the semiconductor MXene material Lu 2 CT 2 (T = F, OH) has a low work function and a carrier mobility of about 105 cm 2 /V at room temperature ( Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 77%
“…In this manner, we can improve the incident light absorption capacity by the photothermal 2D materials. For this, Wang et al [60] developed the Cu 3 BiS 3 (CBS) on Ti 3 C 2 MXene nanosheets (0.2 g) for the first time via the thermal-injection method in the ratio of 1:1 (CBS-Ti 3 C 2 ). Later, this composition at different loadings (0.12, 0.24, 0.48, and 0.60 mg cm −2 ) was placed on a hydrophilic porous filter membrane (PVDF) and vacuum dried overnight.…”
Section: Membranementioning
confidence: 99%
“…Similar to the PVDF membrane interfacial interaction with the Ti 3 C 2 MXene [39,60,61], another study on the Ti 3 C 2 /PVDF membrane was explored by Peng et al [62]. They revealed an efficient air-water interface during solar desalination.…”
Section: Membranementioning
confidence: 99%